A 5-Step Approach Protocol Using CareLink Therapy Software in Type 1 Diabetes Patients - Petrovski, Goran; Zivkovic, Marija (SAGE Publications, 2017)
We have developed a 5-step approach protocol in interpreting SAP using CareLink. The main objective of this pilot study was to assess the usability of the protocol. The main analysis is based on the Therapy Management Dashboard, where five segments are allocated: (1) basic statistics; (2) glucose and insulin overlay; (3) postprandial period; (4) basal/bolus insulin; (5) suspends and sensor. Possible changes are noted on a printed insulin settings page with evaluation of rationale/physiological insulin. Every segment is analyzed with correlation through others with step by step confirmation of possible change. Thirty-four patients (F 18, M 16), age 15.3 ± 7.7 years with total of 128 CareLink downloads were analyzed on monthly basis in a period of 3 months. The patients profile matched our everyday clinical practice, similar to glucose control on patients using insulin pump reported in several studies.3,4 Our data showed increased insulin total daily dose (TDD), due to fine tuning with more bolus dose than the basal rates. The glucose control was improved (as seen in Table 1) with a decreased hyperglycemic and hypoglycemic patterns.A 5-step approach protocol in interpreting SAP using CareLink is simple, convenient, and efficient and should be assessed on the multicenter level and with a wider population.
Keywords: 5-step approach; Protocol; CareLink; Sensor-augmented pump